Investigating the Distribution of Intimin and Invasin in Aeromonas hydrophila and Their Role in Host Tissue Attachment - Agradip Bhattacharyya; Goutam Banerjee; Pritam Chattopadhyay (Bacteria)
Background: Aeromonas hydrophila is a key pathogen affecting freshwater fish, including Labeo rohita (rohu), causing significant aquaculture losses. This study explores the role of intimin and invasin, known virulence factors, in A. hydrophila pathogenesis using in silico methods. Methods: We analyzed the distribution of invasin and intimin across 53 A. hydrophila genomes and examined their physicochemical properties, secondary structures, and 3D models. Since crystal structures were unavailable, homology-based modeling was employed to study the structure of rohu β-integrins. In silico docking was performed to explore the interactions between intimin/invasin and β-integrins. Results: Our findings revealed that intimin and invasin were present in only 6 out of the 53 A. hydrophila strains examined, which were designated as hypervirulent strains. The transmembrane regions of intimin and invasin were modeled as β-barrels, a common feature of porins. The in silico docking experiments indicated the significant binding affinity of invasin and intimin with all the β-integrins of rohu fish, suggesting a critical role in host attachment and cellular internalization. Conclusions: This in silico study highlights the pivotal role of invasin and intimin in host tissue’s binding efficacy, offering valuable insights into the binding potential of A. hydrophila across various organs in rohu fish.